Meningkatkan Jiwa Sadar Wisata Pada Jenjang Sekolah Menengah Atas, Sosialisasi di SMAN 1 Jonggat - Setiawan, Muhamad Alam; Pribadi, Teguh Iman (CV. Global Cendekia Inti, 2024)
Kecamatan Jonggat is a district which consist of several villages that has a huge potential to become village tourist destination. Bonjeruk Village and Sukarara Village are well recognized tourist village existed in Jonggat The tourism awareness of society around is an important thing to be concerned to ensure the sustainability of the tourism industry in the tourist village. The knowledge about pentahelix model is important to realize the society that they are an important part of the tourism in the neighborhood. This article discusses the result of the socialization of tourism awareness toward the youth specifically the students of SMAN 1 Jonggat. The activity is carried out in May 16th 2024 and concluded that the socialization about tourism awareness is needed by the society especially the youth. Tourism awareness education should be intense and done in comprehensive way so that the youth will be fully aware and willing to become agent of tourism in their place.